Etika dan Kekayaan Intelektual dalam Wirausaha: Pilar Keberlanjutan Bisnis Modern - Asrizal, Asrizal; Suyowanto, Suyowanto; Winarno, Agung; Rahayu, Wening Patmi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
the digital and globalization era, entrepreneurs face complex challenges related to intellectual property rights (IPR) violations, such as piracy, brand counterfeiting, and idea theft. This phenomenon not only has an impact on the legal aspect, but also creates significant business ethics dilemmas. This study aims to analyze the relationship between the application of business ethics and IPR protection in the context of entrepreneurship, and to explore how the integration of the two can improve business competitiveness and sustainability. The methodology used is a qualitative literature study with a descriptive-analytical approach, reviewing various sources such as scientific journals, legal regulations related to IPR, and case studies of entrepreneurs who apply ethical principles and IPR protection. The results of the study indicate that the application of strong business ethics has a significant impact on the awareness and compliance of business actors in protecting intellectual property. Meanwhile, an understanding of IPR law can encourage innovation and create a fair and sustainable business climate. This is in accordance with the theory of the application of business ethics, IPR protection and legal protection for consumers have a significant influence on business, emphasizing the importance of integrating the three to support fair and sustainable business practices. This study confirms that the integration of business ethics and IPR protection is not only a formal legal aspect, but also an important strategy in building a positive image, consumer trust, and long-term business sustainability. Therefore, education and awareness of the importance of business ethics and IPR protection need to be increased among entrepreneurs to create a healthy, competitive and sustainable business ecosystem.